CXCL4-induced macrophages in human atherosclerosis - Domschke, Gabriele; Gleißner, Christian A. (Cytokine, 2019)
Atherosclerosis is considered an inflammatory disease of the arterial wall. Monocytes and monocyte-derived cells (most often termed macrophages) play an essential role in the formation of atherosclerotic lesions, as they take up lipids leading to subsequent foam cell formation accompanied by release of pro-inflammatory cytokines. Similarly, platelets have been discovered to represent an important cell type mediating inflammatory and immune processes in atherogenesis, mainly by secreting chemokines, which are stored in the platelets’ alpha granules, upon platelet activation. Therefore, the interaction between monocyte-derived cells and platelets is of exceptional importance. In this review, we specifically focus on the chemokine (platelet factor-4, PF4) and its effects on monocytes and monocyte-derived cells. By formation of heterodimers dimers and -oligomers with CCL5, CXCL4 induces binding of monocytes cells to endothelial cell and thereby promotes diapedesis of monocytes into the subendothelial space. CXCL4 also affects the differentiation of monocytes as it induces a specific macrophage phenotype, which we suggested to term “M4”. For example, CXCL4-induced macrophages irreversibly lose the hemoglobin-haptoglobin scavenger receptor CD163. The combination of CD68, S100A8, and MMP7 turned out to reliably identify M4 macrophages both in vitro and in vivo within atherosclerotic lesions. In human atherosclerotic plaques, M4 macrophages are predominantly present in the adventitia and the intima and their prevalence is associated with plaque instability suggesting that they are a marker of pro-inflammatory activity. Overall, CXCL4-induced M4 macrophages may represent a target for diagnostic and therapeutic interventions in human atherosclerotic disease.